2015
DOI: 10.1002/maco.201408185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic anions on the corrosion behavior of UNS S32750 duplex stainless steel in chloride solution

Abstract: The present study explored the electrochemical behavior of UNS S32750, a super duplex stainless steel which was not commonly researched in previous studies. The effect of bicarbonate (HCO À 3 ) and sulfate (SO 2À 4 ) on the electrochemical behavior of UNS S32750 duplex stainless steel in the chloride (Cl À ) solution was investigated using potentiodynamic polarization, scanning electron microscope (SEM), electrochemical impedance spectroscopy (EIS), and Mott-Schottky analysis. The electrochemistry behavior sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…− addition in the underground water solutions. 7,[10][11][12] In previous studies, some indices, such as LSI, 18,32 RSI, 18,19 and LSCI, 20 were proposed to estimate the corrosive tendencies of underground water for carbon steels. These indices were calculated from Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…− addition in the underground water solutions. 7,[10][11][12] In previous studies, some indices, such as LSI, 18,32 RSI, 18,19 and LSCI, 20 were proposed to estimate the corrosive tendencies of underground water for carbon steels. These indices were calculated from Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, Cl − in the underground water aggravated the corrosion of 201 and 304 austenitic stainless steels, 26,33 whereas SO 4 2− and HCO 3 − inhibited the degradation of 304, 316 austenitic stainless steels, and 32750 duplex stainless steels. 7,[10][11][12] Based on the aforementioned information, a parameter that was termed the composite corrosiveness index (CCI), which included the solution pH information, was proposed to evaluate the corrosive tendency of the underground water on the widely applied austenitic and duplex stainless steels, and the CCI can be calculated from Eq. 5…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a widely used material presenting high strength and corrosion resistance, the corrosion behaviour for 2205 DSS performed in an oceanic atmosphere containing sulphur element, which was due to pollution from industrialisation, plays an important role in marine industrial development. Previous researches [1,5,8,[15][16][17][18][19] found that if there are acid ions containing sulphur such as SO 4 2− , HSO 3 − , etc. in the solution or a thin electrolyte layer, it will hinder the formation of the passive film of steel, because the sulfides synthesised by the S and metals can reduce the stability of the passive film, thus increasing the sensitivity of pitting corrosion for stainless steels.…”
Section: Introductionmentioning
confidence: 99%